Individual and combined toxicological effects of deoxynivalenol and zearalenone on human hepatocytes in in vitro chronic exposure conditions. (5th October 2017) - Smith, Marie-Caroline; Madec, Stéphanie; Pawtowski, Audrey; Coton, Emmanuel; Hymery, Nolwenn
Highlights: DON exposure at the maximum level permitted in cereals led to high cell mortality. The DON + ZEA mixture exhibited similar cytotoxic effects as DON alone. Lower toxin doses induced gene expression level changes for liver-specific factors. The DON + ZEA mixture affected different genes than DON and ZEA individually. Abstract: While numerous surveys highlighted the natural co-occurrence of mycotoxins in food, data about their toxicological combined effects is still limited. This is especially the case for chronic exposure conditions, although the latter are more representative of the mycotoxin risk associated with food consumption than acute exposure. In the present study, cell viability and gene expression levels of relevant hepatocyte-specific functions were evaluated for the HepaRG human liver cell line exposed to deoxynivalenol (DON) and/or zearalenone (ZEA) during 14, 28 and 42 days at three subtoxic concentrations corresponding to i) the determined average exposure dose of French adult population, ii) the tolerable daily intake established by the Joint FAO/WHO Expert Committee and iii) the maximum level permitted by the European regulation in cereals intended for direct human consumption. For the latter, DON and DON + ZEA induced 90% cell mortality after 14 days. In addition, depending on the considered toxin or mixture, doses and exposure periods, important variations of gene expression levels were observed. Despite the fact that in vitro conditions differ from the in vivo situation, the obtained results clearly highlighted that long-term toxicological effects of chronic exposure to mycotoxin combinations should be further investigated and, if necessary, taken into consideration at the regulatory level.